UJIAN ON LINE DALAM E-LEARNING: PERBANDINGAN UJIANONLINE (COMPUTER BASED) TERHADAP UJIAN TRADISIONAL (PAPER BASED) - Yuliyanto, Heri; Wahyuni, Titis; Seputra, Yulius Eka Agung (Jurnal Vokasi Indonesia, 2016)
Spreading the uneven quality education in Indonesia is a national educational problems to be solved. Implementation of quality education largely implemented in Java, in the case of Indonesian citizens spread all over Indonesia, from Sabang to Merauke. All citizens of the Indondesia want to receive a quality education that is easily accessible at reasonable costs. One solution that can be used to solve the problem is e-learning. However, many factors must be considered in the process of long-distance pembejaran known as elearning, one of which is the process of evaluating learning outcomes. This article discusses the process of evaluation of learning outcomes by studying literature several articles published between the years 2007 - 2015 with a focus on expert opinion to the statement "whether the test on line (computer-based) may replace the exam traditional (paper-based)" through the presentation of the pros and cons exam on line. From this study it was found that there are opportunities to replace paper-based exams to computer-based test with due regard to the technical elements such as security, ease of use and ability of computer users base. However, such reimbursement can not be applied to all conditions and the need to pay attention to the learning objectives that have been set. Therefore, further research is needed to develop a model to evaluate student achievement by combining the concept of competency-based assessment cubic online (Cubiks Online Asesessment) by combining multiple information security concepts.